Access and Barriers to Online Education for People with Disabilities - Kent, Michael (National Centre for Student Equity in Higher Education, 2016)
This paper reports on a study conducted in 2014 and 2015 that explored the accessibility of eLearning for students with disabilities studying fully online in Australia. The study looked at students studying through Open Universities Australia (OUA). OUA brings together 15 different independent higher education institutions to teach students fully online across a number of different fields. This diversity of institutions allowed a number of different eLearning environments, technologies and learning and teaching strategies to be canvassed. The study had two phases. Firstly, a survey that explored students’ experience related to the accessibility of online learning and teaching platforms, and students’ approach to disclosure of their disability and the effectiveness of any accommodation offered by the different institutions. The survey had 356 responses. The second phase of the research consisted of a series of 143 interviews that expanded on the information collected in the surveys and also explored the accessibility of different approaches to learning and teaching and assessment. Open Universities Australia invites students to nominate one of eight broad impairment categories when they identify themselves as a person with a disability these categories – mental illness, medical impairment, mobility impairment, hearing impairment, learning disability, vision impairment, acquired brain impairment (ABI) and intellectual disability – were used in the survey and interviews to provide different perspectives from students with these different impairment types. Each of these eight broad categories is individually addressed in this report. The findings of this research indicated that student with disabilities found that online study through OUA was a preferred way to access higher education. There was an unexpectedly high incidence of students with a mental illness (44.9% of survey respondents) and medical impairments (39.2% of survey respondents), with mobility impairments rounding out the top three categories (25.3% of survey respondents). The finding of this prevalence was one of the major findings of this study, along with the impact of different impairments on learning technologies, learning and teaching strategies and attitudes towards disclosure. The report presents a number of recommendations related to policy and compliance, staff training, unit design, and assessment design and implementation. It also calls for further directions for research including the development of universal design in eLearning, and the need for further research to provide a voice for staff at universities in relation to access for students with disabilities.